Pathogenic variant profile in DNA damage response genes correlates with metastatic breast cancer progression-free survival in a Mexican-mestizo population - Vázquez-Romo, Rafael; Millan-Catalan, Oliver; Ruíz-García, Erika; Martínez-Gutiérrez, Antonio D.; Alvarado-Miranda, Alberto; Campos-Parra, Alma D.; López-Camarillo, César; Jacobo-Herrera, Nadia; López-Urrutia, Eduardo; Guardado-Estrada, Mariano; Cantú de León, David; Pérez-Plasencia, Carlos (Frontiers in Oncology, 2023)
Metastatic breast cancer most breast-cancer related deaths around the world, especially in countries where breast cancer is detected in late into its development. Genetic testing for cancer susceptibility started with the BRCA 1 and 2 genes, but recent research has shown that mutations in other members of the DNA damage response (DDR) are also associated with elevated cancer risk, opening new opportunities for enhanced genetic testing strategies. We sequenced BRCA1/2 and twelve other DDR genes from a Mexican-mestizo population of 40 metastatic breast cancer patients through semiconductor sequencing. Overall, we found 22 mutations –9 of them reported for the first time– and a strikingly high proportion of mutations in ARID1A. Mutations in the ARID1A, BRCA1, BRCA2, and FANCA genes were significantly associated with higher progression-free survival in our patient cohort. Thus, our results reflected the unique characteristics of the Mexican-mestizo population as the proportion of mutations we found differ from that of other global populations. Based on these findings, we suggest routine screening for mutations in ARID1A along with BRCA1/2 in breast cancer patients from the Mexican-mestizo population.